Step-by-step Solution

Solve the differential equation $dx+e^{3x}dy=0$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Step-by-step explanation

Problem to solve:

$dx+e^{3x}dy=0$

Learn how to solve differential equations problems step by step online.

$e^{3x}dy=-dx$

Unlock this full step-by-step solution!

Learn how to solve differential equations problems step by step online. Solve the differential equation dx+e^(3x)dy=0. We need to isolate the dependent variable y, we can do that by subtracting dx from both sides of the equation. Group the terms of the differential equation. Move the terms of the y variable to the left side, and the terms of the x variable to the right side. Integrate both sides of the differential equation, the left side with respect to y, and the right side with respect to x. Solve the integral \int1dy and replace the result in the differential equation.

Final Answer

$y=\frac{1}{3e^{3x}}+C_0$